Aurora kinase A-mediated phosphorylation of mPOU at a specific site drives skeletal muscle differentiation. (30th October 2019) - Karthigeyan, Dhanasekan; Bose, Arnab; Boopathi, Ramachandran; Rao, Vinay Jaya; Shima, Hiroki; Bharathy, Narendra; Igarashi, Kazuhiko; Taneja, Reshma; Trivedi, Arun Kumar; Kundu, Tapas K
Abstract: Aurora kinases are Ser/Thr-directed protein kinases which play pivotal roles in mitosis. Recent evidences highlight the importance of these kinases in multiple biological events including skeletal muscle differentiation. Our earlier study identified the transcription factor POU6F1 (or mPOU) as a novel Aurora kinase (Aurk) A substrate. Here, we report that Aurora kinase A phosphorylates mPOU at Ser197 and inhibit its DNA-binding ability. Delving into mPOU physiology, we find that the phospho-mimic (S197D) mPOU mutant exhibits enhancement, while the wild type or the phospho-deficient mutant shows retardation in C2C12 myoblast differentiation. Interestingly, POU6F1 depletion phenocopies S197D-mPOU overexpression in the differentiation context. Collectively, our results signify mPOU as a negative regulator of skeletal muscle differentiation and strengthen the importance of AurkA in skeletal myogenesis.